2001
DOI: 10.1002/ajmg.10009
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural genetic counseling: Then, now, and in the 21st century

Abstract: Scholars, educators, and practitioners have argued that racial-cultural issues are obstacles for those seeking genetic counseling. When available, cross-cultural genetic counseling has focused on simplistic knowledge of client health beliefs and cultural customs, professional cultures, and biased theoretical models as reasons for failure to create realistic knowledge of members of racial-cultural groups in the United States. Recognizing the importance of meeting the needs for all who seek genetic counseling se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…As described earlier, this research builds upon the evolving field of multicultural genetic counseling and transitions away from the assessment of traditionally visible racial and cultural groups to understand a more fully integrated cognitive-affective racial and cultural identity. From this multicultural perspective, greater consideration is given to the range of variation among racial and cultural groups [30]. In fact, a review of existing literature related to genetic counseling by Wang [30] found that only 9% of articles discussed cultural issues; meanwhile, amongst those few who did, 75% considered a cross-cultural, group-specific approach rather than one which values understanding variation among group members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As described earlier, this research builds upon the evolving field of multicultural genetic counseling and transitions away from the assessment of traditionally visible racial and cultural groups to understand a more fully integrated cognitive-affective racial and cultural identity. From this multicultural perspective, greater consideration is given to the range of variation among racial and cultural groups [30]. In fact, a review of existing literature related to genetic counseling by Wang [30] found that only 9% of articles discussed cultural issues; meanwhile, amongst those few who did, 75% considered a cross-cultural, group-specific approach rather than one which values understanding variation among group members.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a review of existing literature related to genetic counseling by Wang [30] found that only 9% of articles discussed cultural issues; meanwhile, amongst those few who did, 75% considered a cross-cultural, group-specific approach rather than one which values understanding variation among group members. The study results presented here, which treat ethnic, racial and cultural identity as distinct, but closely related constructs, thus, uniquely add to the multicultural counseling literature by following the shift from exploring race alone to understanding the impact of ethnic, racial and cultural identities [30,36,39]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes the utilization of a cultural broker (someone familiar with the culture and language of both the clinical team as well as that of the target population, who can help bridge the cultural and linguistic differences) vitally important because genetic counseling is predicated on effective communication and building rapport (Jezewski and Sotnik 2001; Kowal et al 2015; Mittman et al 1998; Penn et al 2010; Port et al 2008). Recognition, acceptance, and incorporation of cultural differences into the genetic counseling session optimize the delivery of appropriate care (Catz et al 2005; Chapple et al 1995; Richards and Ponder 1996; Sue and Sue 2015; Wang and Marsh 1992; Wang 2001; Weil and Mittman 1993; Weil 2001). …”
Section: Introductionmentioning
confidence: 99%